"Ain't Got Enough Money to Pay Me Respect": Blackfishing, Cultural Appropriation, and the Commodification of Blackness. (October 2021) - Cherid, Maha Ikram
The term blackfishing, which takes a twist on the concept of catfishing, that is, tricking people online into thinking you are someone else, refers to the practice of (mostly) White women pretending to be Black by using makeup, hairstyles, and fashion that originate in Black Culture to gain financial benefits. This article aims to contextualize the concept of blackfishing through a critical literary review that will cover the following elements: cultural appropriation, the commodification of Black culture, the representation of Black women in North America, and the operationalization of blackfishing.